2022
DOI: 10.1002/ecs2.4037
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of fungal and bacterial microbiomes on rainforest frogs following a disease outbreak

Abstract: Emerging infectious diseases are a serious threat to wildlife populations, and there is growing evidence that host microbiomes play important roles in infection dynamics, possibly even mitigating diseases. Nevertheless, most research on this topic has focused only on bacterial microbiomes, while fungal microbiomes have been largely neglected. To help fill this gap in our knowledge, we examined both the bacterial and fungal microbiomes of four sympatric Australian frog species, which had different population‐le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…It has been shown that Bd presence have contrasting effects over skin microbiota diversity inducing changes in skin microbiota composition following infection [ 21 , 23 , 71 ] or not influencing diversity of skin microbial communities [ 42 , 44 ] as we found in this study. However, it also has been shown that relative abundances of some bacterial members of the skin microbiota correlates with chytrid infection intensity [ 19 , 44 , 45 ] and its suggested that according to the type of correlation these groups could act as anti Bd bacteria [ 19 ].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It has been shown that Bd presence have contrasting effects over skin microbiota diversity inducing changes in skin microbiota composition following infection [ 21 , 23 , 71 ] or not influencing diversity of skin microbial communities [ 42 , 44 ] as we found in this study. However, it also has been shown that relative abundances of some bacterial members of the skin microbiota correlates with chytrid infection intensity [ 19 , 44 , 45 ] and its suggested that according to the type of correlation these groups could act as anti Bd bacteria [ 19 ].…”
Section: Discussionsupporting
confidence: 68%
“…Considering that the main source of diversity of the skin microbiota are the environmental microbial communities and that they vary in response to environmental variation [ 65 67 ] it is likely that the skin microbiota reflect to some extent the environmental variations across localities as seen in the case of pre-metamorphic axolotls. It has been shown that skin bacterial diversity vary in response to precipitation [ 19 , 23 ] temperature [ 22 ] or elevation gradients [ 24 , 41 , 42 ]. However, genetic differences across populations could also explain some of our results, since a previous study showed that A. altamirani populations of sites 2 and 3 are genetically differentiated [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the clr-transformation based methods might overestimate tested effects: these methods do not account for uneven library size across samples (Kaul et al, 2017), potentially magnifying differences among samples. Log-transformation based methods likely to exaggerate the importance of rare taxa, while rarefaction or proportion based methods, which fully normalize read depths across samples, may be superior to log-transformation based methods for comparing ecological communities (McKnight et al 2019). Although developed for differential abundance testing, ANCOM-BC methods outperformed other normalization methods, including the proportion-based method proposed by McKnight et al (2019), for the visualization of separate samples from different populations (Lin & Peddada, 2020).…”
Section: Downstream Marker-gene Data-analysis Methodsmentioning
confidence: 99%
“…Log-transformation based methods likely to exaggerate the importance of rare taxa, while rarefaction or proportion based methods, which fully normalize read depths across samples, may be superior to log-transformation based methods for comparing ecological communities (McKnight et al 2019). Although developed for differential abundance testing, ANCOM-BC methods outperformed other normalization methods, including the proportion-based method proposed by McKnight et al (2019), for the visualization of separate samples from different populations (Lin & Peddada, 2020). It is beyond the scope of the present study to statistically demonstrate the superiority of ANCOM-BC based methods, but our results do highlight the impacts of analyzing marker-gene data using different data normalization methods as well as the potential weaknesses of rarefaction-and log-transformation based methods for analyzing nematode HTS data.…”
Section: Downstream Marker-gene Data-analysis Methodsmentioning
confidence: 99%